Cook real Hawaiʻi - Simeon, Sheldon; Snyder, Garrett (Clarkson Potter/Publishers, 2021)
"The story of Hawaiian cooking, by a two-time Top Chef finalist and Fan Favorite, through 100 recipes that embody the beautiful cross-cultural exchange of the islands. On two seasons of Top Chef, Sheldon Simeon established himself as a leading young, creative chef (he was both a finalist and Fan Favorite on both seasons). The role he is even more proud to fill, though, is as the storyteller of Hawaiian cuisine and the many cultures that have come together there to create it: the native Hawaiian traditions, Japanese influences, Portuguese cooking techniques, and dynamic flavors that are closest to Sheldon's heart"--